A method for preparing a polyetheretherketone-based composite coating for improving the tribological properties of aviation hydraulic pump friction pairs
By preparing a polyether ether ketone-based composite coating on the friction pair of the aviation hydraulic pump, the bonding strength between the coating and the substrate is improved by rolling and hot pressing processes, the friction wear problem of the friction pair of the aviation hydraulic pump under the aviation kerosene medium is solved, and the tribological performance is significantly improved.
Patent Information
- Application Number
- CN202310789082.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-30
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2043-06-30
AI Technical Summary
The friction wear problem of the friction pair of the aviation hydraulic pump under the aviation kerosene medium is relatively prominent, and the prior art is difficult to effectively improve its tribological performance.
The polyether ether ketone-based composite coating is prepared by mixing the polyether ether ketone powder with filler particles, adding polytetrafluoroethylene emulsion and polyamide imide dispersion to form a plastic mud material, and closely bonding it with the copper powder layer through rolling and hot pressing processes to prepare a high-performance polyether ether ketone-based composite coating.
The tribological properties of the friction pair under aviation kerosene medium are significantly improved, the ultimate load is increased by 50%, and the average friction coefficient and wear rate are reduced by more than 45%.
Smart Images

Figure BDA0004313111080000051 
Figure HDA0004313111090000011 
Figure HDA0004313111090000021
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of surface coatings, and in particular to a method for preparing a polyetheretherketone-based composite coating for improving the tribological performance of a friction pair of an aviation hydraulic pump. Background Art
[0002] The aviation hydraulic pump is the core component of the aircraft hydraulic system. Its performance directly determines the performance of the aircraft hydraulic system, and the life and reliability of the aviation hydraulic pump directly depend on the hydraulic pump friction pair. The aviation hydraulic pump uses aviation kerosene as the working medium. Compared with traditional hydraulic oil, aviation kerosene has low viscosity and poor lubrication performance, and can also be used as a cleaning agent. The lower viscosity will cause the leakage of the aviation hydraulic pump to increase and reduce its volumetric efficiency; the poor lubrication performance makes it poor in forming an oil film between the friction pairs; the cleaning function of aviation kerosene will also clean the adhesion of the friction interface, which is not conducive to friction and wear. Therefore, the friction and wear problem of the aviation hydraulic pump friction pair under the aviation kerosene medium is an urgent problem to be solved.
[0003] In recent years, the preparation of high-performance polyetheretherketone-based composite coatings on the surface of friction pairs to improve their tribological properties has received widespread attention. Polyetheretherketone (PEEK) is a semi-crystalline aromatic thermoplastic engineering plastic with excellent high temperature resistance, flexibility, processability and corrosion resistance. In addition, polyetheretherketone is a perfect combination of rigidity and toughness, and the performance of polyetheretherketone modified with filler particles can be further improved. Common filler particles mainly include lubricating particles such as polytetrafluoroethylene, graphite and tungsten disulfide, as well as hard particles such as silicon dioxide, silicon carbide and aluminum oxide. However, how to accurately control the coating preparation, improve the dispersibility of these filler particles in polyetheretherketone, and improve the bonding strength between the polyetheretherketone-based composite coating and the substrate, so as to improve the tribological performance of the friction pair under the medium of aviation kerosene, are all unresolved problems.
[0004] Common preparation methods for polyetheretherketone-based composite coatings include air spraying, electrostatic spraying, and thermal spraying. During the air spraying process, paint splashing will occur, resulting in low utilization of the paint, a large impact on the surrounding environment, and overspray or fog paint, resulting in defects on the coating surface; electrostatic spraying has a high fire hazard; thermal spraying has a low material utilization rate, and the prepared coating has a high porosity and low bonding strength with the substrate. A Chinese patent (CN202111335207.0) reports a modified PEEK-based self-lubricating three-layer composite material and a molding method thereof. The thickness of the composite material needs to be regulated by three steps of rolling, intermediate rolling, and hot rolling. The process is relatively cumbersome. In addition, the fluidity of the molten polymer is poor during the plasticization process, which is not conducive to the crystallization of the composite material and has a significant impact on the material properties. Therefore, it is necessary to develop a method for preparing a polyetheretherketone-based composite coating that improves the tribological properties of the friction pair of an aviation hydraulic pump to solve the above problems. Summary of the invention
[0005] In view of the problems existing in the prior art, the purpose of the present invention is to provide a method for preparing a polyetheretherketone-based composite coating, so as to achieve precise preparation of the coating, improve the dispersibility of the filling particles in the polyetheretherketone, enhance the bonding strength between the polyetheretherketone-based composite coating and the substrate, and improve the tribological properties of the friction pair in the aviation kerosene medium.
[0006] In order to achieve the above object, the present invention is implemented by the following technical solutions:
[0007] A method for preparing a polyetheretherketone-based composite coating for improving the tribological properties of a friction pair of an aviation hydraulic pump is prepared according to the following steps, calculated by mass:
[0008] (1) 17-23 parts of polyetheretherketone powder and 3-7 parts of filler particles are mixed uniformly to form a mixed phase; 22-28 parts of polytetrafluoroethylene emulsion and 2-4 parts of polyamideimide dispersion are stirred uniformly to form a stirred phase; during the stirring process, the mixed phase is added to the stirred phase, and then 5-9 parts of anhydrous ethanol are added to demulsify to obtain a plastic mud;
[0009] (2) The plastic mud is evenly spread on the copper-steel bimetallic ball powder plate, and then it is rolled through a double-roller finishing mill with a rolling mill gap of 1.9-2.2 mm, and then the rolled ball powder plate is baked at 140-160° C. for 10-30 minutes;
[0010] (3) 1-5 parts of a semi-permanent mold release agent is evenly applied on the upper heating plate of a hot press, and then the baked ball powder plate is placed on the lower heating plate of the hot press. Then, the plastic mud is plasticized and tightly combined with the copper powder layer at a hot pressing temperature of 355-380°C, a hot pressing pressure of 2-6MPa, and a hot pressing time of 10-30min. When the hot press is cooled to 180-200°C, the ball powder plate is taken out to obtain a polyetheretherketone-based composite coating.
[0011] Further specific technical solutions are as follows:
[0012] The average particle size of the polyetheretherketone powder in step (1) is 40-60 μm; the average particle size of the polytetrafluoroethylene emulsion is 0.2-0.4 μm, and the solid content is 55-65%; the solid content of the polyamideimide dispersion is 16-24%; and the filling particles are graphite with an average particle size of 10-20 μm.
[0013] Compared with the prior art, the present invention has the following beneficial effects:
[0014] 1. The present invention prepares a polyetheretherketone-based composite coating by hot pressing a plastic mud onto a copper-steel bimetallic ball powder plate, and precisely controls the coating by changing the rolling method. Compared with the commonly used preparation methods, the present invention has uniform dispersion of filling particles, controllable coating thickness, and good coating surface quality; there is no splashing of paint, the utilization rate of the plastic mud is high, and the impact on the surrounding environment is small; the preparation process is safe and simple.
[0015] 2. The coating preparation method of the present invention can enhance the fluidity of the molten polymer and significantly improve the crystallinity of the polymer through the plasticization process of the polyetheretherketone composite material induced by pressure, thereby significantly improving the bonding strength between the components of the coating and the hardness of the coating.
[0016] 3. The polyetheretherketone and graphite in the polyetheretherketone-based composite coating prepared by the present invention are evenly distributed in the grid of the reticulated polytetrafluoroethylene. After rolling and hot pressing, the plastic mud can be well embedded in the gaps between the copper powder particles of the ball powder plate and tightly combined with the matrix, which significantly improves the friction and wear service life in the aviation kerosene medium.
[0017] 4. Compared with existing products on the market, the polyetheretherketone-based composite coating prepared by the present invention can significantly improve the tribological properties of aviation hydraulic pump friction pairs, wherein the limit load is increased by 50%, and the average friction coefficient and wear rate are reduced by more than 45%. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 The SEM image (a), EDS spectrum (b), regional EDS spectrum (c, d) and element distribution diagram (eg) of the surface of the polyetheretherketone-based composite coating prepared in Example 1 of the present invention;
[0019] Figure 2 The SEM image (a) of the cross section of the polyetheretherketone-based composite coating prepared in Example 1 of the present invention and the SEM image (b) of a partially enlarged cross section of the coating;
[0020] Figure 3 The XRD spectrum of the polyetheretherketone-based composite coating prepared in Example 1 of the present invention;
[0021] Figure 4 The SEM image (a) and EDS spectrum (b) of the wear surface of the polyetheretherketone-based composite coating prepared in Example 1 of the present invention; DETAILED DESCRIPTION
[0022] In order to better understand the present invention, the present invention is described by the following specific examples, but these examples do not limit the present invention. The average particle size of the polyetheretherketone powder described in the following examples is 50 μm; the average particle size of the polytetrafluoroethylene emulsion is 0.25 μm, and the solid content is 60%; the solid content of the polyamide-imide dispersion is 20%; and the average particle size of the graphite is 14 μm.
[0023] Example 1
[0024] A method for preparing a polyetheretherketone-based composite coating for improving the tribological properties of a friction pair of an aviation hydraulic pump is prepared according to the following steps, calculated by mass:
[0025] (1) 20 parts of polyetheretherketone powder and 4.98 parts of graphite are mixed uniformly to form a mixed phase; 25 parts of polytetrafluoroethylene emulsion and 3 parts of polyamideimide dispersion are stirred uniformly to form a stirred phase; during the stirring process, the mixed phase is added to the stirred phase, and then 7 parts of anhydrous ethanol is added to demulsify, thereby obtaining a plastic mud;
[0026] (2) The plastic mud is evenly spread on the copper-steel bimetallic ball powder plate, and then it is rolled through a double-roller finishing mill with a rolling mill gap of 1.9 mm, and then the rolled ball powder plate is baked at 150° C. for 20 minutes;
[0027] (3) 3 parts of semi-permanent mold release agent are evenly applied on the upper heating plate of the hot press, and then the baked ball powder plate is placed on the lower heating plate of the hot press. Then, the plastic mud is plasticized and tightly combined with the copper powder layer under the hot pressing temperature of 370°C, the hot pressing pressure of 4MPa, and the hot pressing time of 30min. When the hot press is cooled to 180°C, the ball powder plate is taken out to obtain a polyetheretherketone-based composite coating, which is marked as 14C / PTFE / PEEK 1.9 .
[0028] Depend on Figure 1 (a) It can be seen that 14C / PTFE / PEEK 1.9 The coating surface is relatively smooth and has no obvious defects; Figure 1 (b) It can be seen that 14C / PTFE / PEEK 1.9 The coating is mainly composed of three elements: C, F, and O. The C element comes from graphite, polyetheretherketone and polytetrafluoroethylene, the F element comes from polytetrafluoroethylene, the O element comes from polyetheretherketone, and a small amount of Si element comes from the semi-permanent release agent applied during the coating preparation process. Figure 1 (c) It can be seen that the element composition of the larger black area on the coating surface is C and O, indicating that the larger black particles are polyetheretherketone; Figure 1(d) It can be seen that the element composition of the gray area containing smaller black particles on the coating surface is C and F, and the content of C element is higher than that of F element, which means that the gray area is polytetrafluoroethylene and contains graphite. Figure 1 (eg) It can be seen that the distribution of polytetrafluoroethylene is like a net, and graphite and polyetheretherketone are evenly distributed in the grid.
[0029] Depend on Figure 2 (a) It can be seen that 14C / PTFE / PEEK 1.9 The coating thickness is 387 μm, and there is a clear boundary between the coating and the substrate. After rolling and hot pressing, the plastic mud can be well embedded in the gap between the copper powder particles and closely combined with the substrate. Figure 2 b) It can also be seen that polyetheretherketone and graphite are evenly distributed in the grid of the reticulated polytetrafluoroethylene.
[0030] Made of 14C / PTFE / PEEK 1.9 XRD patterns of the coatings ( Figure 3 ) shows that the composite coating has a polytetrafluoroethylene diffraction peak at about 18.1°, a polyetheretherketone diffraction peak at about 18.9°, and a graphite diffraction peak at about 26.6°, which indicates that 14C / PTFE / PEEK 1.9 The coating contains polytetrafluoroethylene, polyetheretherketone and graphite. In addition, the composite coating has a copper diffraction peak of copper powder particles at about 42.8°. Figure 3 It can also be found that the intensity of the diffraction peak of polytetrafluoroethylene is stronger than that of the diffraction peak of polyetheretherketone. This is because during the hot pressing process, polytetrafluoroethylene will flow to the surface, resulting in relatively more polytetrafluoroethylene on the surface, and therefore has a stronger diffraction peak intensity.
[0031] Example 2
[0032] A method for preparing a polyetheretherketone-based composite coating for improving the tribological properties of a friction pair of an aviation hydraulic pump is prepared according to the following steps, calculated by mass:
[0033] (1) 18 parts of polyetheretherketone powder and 4.49 parts of graphite are mixed uniformly to form a mixed phase; 22.5 parts of polytetrafluoroethylene emulsion and 2.7 parts of polyamideimide dispersion are stirred uniformly to form a stirred phase; during the stirring process, the mixed phase is added to the stirred phase, and then 6.3 parts of anhydrous ethanol is added to demulsify, thereby obtaining a plastic mud;
[0034] (2) The plastic mud is evenly spread on the copper-steel bimetallic ball powder plate, and then it is rolled through a double-roller finishing mill with a rolling mill gap of 2.2 mm, and then the rolled ball powder plate is baked at 140° C. for 30 minutes;
[0035] (3) 4 parts of semi-permanent mold release agent are evenly applied on the upper heating plate of the hot press, and then the baked ball powder plate is placed on the lower heating plate of the hot press. Then, the plastic mud is plasticized and tightly combined with the copper powder layer under the hot pressing temperature of 370°C, the hot pressing pressure of 4MPa, and the hot pressing time of 30min. When the hot press is cooled to 190°C, the ball powder plate is taken out to obtain a polyetheretherketone-based composite coating, which is marked as 14C / PTFE / PEEK 2.2 .
[0036] Example 3
[0037] A method for preparing a polyetheretherketone-based composite coating for improving the tribological properties of a friction pair of an aviation hydraulic pump is prepared according to the following steps, calculated by mass:
[0038] (1) 27.5 parts of polytetrafluoroethylene emulsion and 3.3 parts of polyamide-imide dispersion were stirred uniformly to form a stirring phase; during the stirring process, 22 parts of polyetheretherketone powder was added to the stirring phase, and then 7.7 parts of anhydrous ethanol was added to break the emulsion to obtain a plastic mud;
[0039] (2) The plastic mud is evenly spread on the copper-steel bimetallic ball powder plate, and then it is rolled through a double-roller finishing mill with a rolling mill gap of 1.9 mm, and then the rolled ball powder plate is baked at 150° C. for 15 minutes;
[0040] (3) 5 parts of semi-permanent mold release agent are evenly applied on the upper heating plate of the hot press, and then the baked ball powder plate is placed on the lower heating plate of the hot press. Then, the plastic mud is plasticized and tightly combined with the copper powder layer at a hot pressing temperature of 370°C, a hot pressing pressure of 4MPa, and a hot pressing time of 30min. When the hot press is cooled to 200°C, the ball powder plate is taken out to obtain a polyetheretherketone-based composite coating, which is marked as PTFE / PEEK. 1.9 .
[0041] Comparative Example 1
[0042] This comparative example uses a polyetheretherketone-based composite coating currently available on the market as a control, which is marked as PEEK AS , prepared by air spraying, using water-based paint.
[0043] Comparative Example 2
[0044] A method for preparing a polyetheretherketone-based composite coating for improving the tribological properties of a friction pair of an aviation hydraulic pump is prepared according to the following steps, calculated by mass:
[0045] (1) 27.5 parts of polytetrafluoroethylene emulsion and 3.3 parts of polyamide-imide dispersion were stirred uniformly to form a stirring phase; during the stirring process, 22 parts of polyetheretherketone powder was added to the stirring phase, and then 7.7 parts of anhydrous ethanol was added to break the emulsion to obtain a plastic mud;
[0046] (2) The plastic mud is evenly spread on the copper-steel bimetallic ball powder plate, and then rolled through a double-roller finishing mill with a mill gap of 1.8 mm. The polyetheretherketone-based composite coating obtained at this time is marked as PTFE / PEEK 1.8 .
[0047] PTFE / PEEK 1.8 The coating surface wrinkles after rolling. This is mainly because the mill gap value is too small at this time, and the rolling force on the coating surface is too large, which causes the surface to be damaged. Therefore, for PTFE / PEEK 1.8 The coatings were no longer subjected to tribological tests.
[0048] In order to demonstrate the effect of the present invention on improving the tribological properties of the friction pair of an aviation hydraulic pump, the 14C / PTFE / PEEK prepared in Example 1 was subjected to 1.9 The coating was subjected to tribological experiments. The experimental conditions were as follows: the experiment was conducted on an end face friction and wear tester using a constant speed step-by-step loading method with oil circulation. The friction pair material used was Cr12, the lubricating medium used was 3# aviation kerosene, the speed was set to 1392rpm, and the corresponding linear speed was 4m / s. The specific method of step-by-step loading was an initial load of 200N, running-in for 3min, and then loading 200N every 3min until the friction torque reached 5N·m or the temperature of the friction interface reached 120℃, and the experiment ended. The ultimate load that the coating can withstand is the previous load at the end of the tribological experiment.
[0049] In addition, the 14C / PTFE / PEEK prepared in Example 2 2.2 Coating, PTFE / PEEK prepared in Example 3 1.9 Coating and PEEK available on the market in Comparative Example 1 AS The coating was also subjected to tribological tests under the above conditions, and the experimental results are shown in Table 1.
[0050] Table 1 Tribological test results of different polyetheretherketone based composite coatings
[0051]
[0052] From the tribological test results in Table 1, it can be seen that the polyetheretherketone-based composite coatings prepared in Example 1, Example 2 and Example 3 have better load-bearing capacity and tribological properties than those in Comparative Example 1. 1.9The coating has the highest limit load, the lowest average friction coefficient and the lowest wear rate. AS Compared with coating, 14C / PTFE / PEEK 1.9 The coating's ultimate load is increased by 50%, the average friction coefficient is reduced by 54%, and the wear rate is reduced by 47%. This is mainly due to the excellent lubrication effect of the filled particle graphite, the easy formation of polytetrafluoroethylene transfer film, thereby reducing the friction coefficient and wear rate, and the addition of graphite can also improve the coating's load-bearing capacity. 2.2 Compared with coating, 14C / PTFE / PEEK 1.9 The coating's ultimate load increased by 16%, the average friction coefficient decreased by 39%, and the wear rate decreased by 25%, mainly due to the 14C / PTFE / PEEK 1.9 The coating is thinner and has better thermal conductivity, which is beneficial for the circulating oil to take away the heat generated by the friction interface, so that the coating has better tribological properties. 1.9 Compared with coating, 14C / PTFE / PEEK 1.9 The coating's ultimate load was increased by 20%, the average friction coefficient was reduced by 31%, and the wear rate was reduced by 29%, mainly due to the 14C / PTFE / PEEK 1.9 The coating contains graphite which provides excellent lubrication and increases load-bearing capacity. Figure 4 It can be seen that 14C / PTFE / PEEK 1.9 The wear surface of the coating has adhesion blocks and a small amount of peeling pits along the sliding direction, and the main wear mechanism is slight adhesive wear and fatigue wear. In summary, the polyetheretherketone-based composite coating prepared by the present invention can significantly improve the tribological properties of the friction pair of the aviation hydraulic pump.
Claims
1. A method for preparing a polyetheretherketone-based composite coating for improving the tribological performance of an aviation hydraulic pump friction pair, characterized in that: The polyetheretherketone-based composite coating is prepared according to the following steps, in parts by mass: (1) 17-23 parts of polyetheretherketone powder and 3-7 parts of filler particles are mixed uniformly to form a mixed phase; 22-28 parts of polytetrafluoroethylene emulsion and 2-4 parts of polyamideimide dispersion are stirred uniformly to form a stirred phase; during the stirring process, the mixed phase is added to the stirred phase, and then 5-9 parts of anhydrous ethanol are added to demulsify to obtain a plastic mud; (2) The plastic mud is evenly spread on the copper-steel bimetallic ball powder plate, and then it is rolled through a double-roller finishing mill with a rolling mill gap of 1.9-2.2 mm, and then the rolled ball powder plate is baked at 140-160° C. for 10-30 minutes; (3) 1-5 parts of a semi-permanent mold release agent is evenly applied on the upper heating plate of a hot press, and then the baked ball powder plate is placed on the lower heating plate of the hot press, and then the plastic mud is plasticized and tightly combined with the copper powder layer at a hot pressing temperature of 355-380° C., a hot pressing pressure of 2-6 MPa, and a hot pressing time of 10-30 min. When the hot press is cooled to 180-200° C., the ball powder plate is taken out to obtain a polyetheretherketone-based composite coating; The average particle size of polyetheretherketone powder is 40-60 μm; the average particle size of polytetrafluoroethylene emulsion is 0.2-0.4 μm, and the solid content is 55-65%; the solid content of polyamideimide dispersion is 16-24%; and the filling particles are graphite with an average particle size of 10-20 μm.
Citation Information
Patent Citations
Modified PEEK-based self-lubricating three-layer composite material and forming method thereof
CN113978059A